(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Objective. To develop and substantiate an optimized approach to the treatment of acute purulent periostitis of the jaws through differentiated prescription of nonsteroidal anti-inflammatory drugs (NSAIDs) based on the severity of pain syndrome and indicators of local immune response.